PENGGUNAAN APLIKASI CROCODILE UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK PADA MATERI LISTRIK DINAMIS - Sunardi Sunardi (Vidya Karya, 2018)
Abstract. This classroom action research aimed to increase teacher activities, students’s activities and interests in science learning on Dynamic Electrical materials using Crocodile application program. The research was conducted in SMPN 1 Banjarmasin, academic year 2016-2017. The subjects of the study were Science Teachers and students of SMPN 1 Banjarmasin. The object of the research are teacher’s activities, students’ activities, and students’ interest in learning science on Dynamic Electric materials. This study consisted of 2 cycles, each cycle consists of two learning activities sections. The data was collected using an observation sheet, a questionnaire, and an achievement test. The data was analyzed using percentage and qualitatively descripted. The research showed that there are increasing in teacher and student activities which was marked by less time to prepare experiment. There was also an increasing in students’ interest showed by 28.57% of students are fun with the science learning and 22,73% of students are interested in learning science. Based on the result, it can be concluded that science learning on Dynamic Electrical material by using Crocodile application program can increase teacher activities, student activities, and student's interest in IX F grade SMP Negeri 1 Banjarmasin in 1st semester of  academic year 2016-2017. Keywords: Crocodile Applications, teacher activities, student activities, Interest in learning Abstrak. Penelitian Tindakan Kelas ini bertujuan untuk meningkatan aktivitas guru, serta aktivitas  dan minat peserta didik dalam pembelajaran IPA pada materi Listrik Dinamis menggunakan program aplikasi Crocodile. Penelitian dilakukan SMP Negeri 1 Banjarmasin, Tahun Pelajaran 2016-2017. Subjek penelitian adalah Guru IPA SMP Negeri 1 Banjarmasin dan ….orang peserta didik kelas IXF. Objek penelitian adalah aktivitas guru, aktivitas peserta didik, dan minat belajar peserta didik pada pembelajaran materi Listrik Dinamis. Penelitian terdiri dari 2 siklus, masing-masing terdiri atas dua kali tatap muka. Instrumen penelitian menggunakan lembar observas, angket dan tes hasil belajar. Data dianalisis menggunakan Teknik persentase dan dideskripsikan secara kualitatif. Hasil Penelitian menunjukkan adanya peningkatan aktivitas guru dan peserta didik yang ditandai dengan berkurangnya waktu penyiapan praktikum. Terjadi juga peningkatan minat peserta didik di mana 28,57% peserta didik senang dengan pembelajaran IPA dan 22,73% peserta didik tertarik dengan pembelajaran IPA. Berdasarkan hasil penelitian dapat disimpulkan bahwa pembelajaran IPA pada materi Listrik Dinamis dengan menggunakan program aplikasi Crocodile dapat meningkatkan aktivitas guru, aktivitas peserta didik, dan minat peserta didik di kelas IX F SMP Negeri 1 Banjarmasin.  Kata kunci: program aplikasi Crocodile, aktivitas guru, aktivitas peserta didik, minat belajar